White Jihad: How White Supremacists Adopt Jihadi Narratives, Aesthetics, and Tactics - Koch, Ariel (Terrorism and political violence, 2024)
This article explores the growing trend of “white jihad” by examining how white supremacists have incorporated jihadi language, motifs, and tactics into their ecosystem. Using observation and content analysis of various primary sources associated with the neo-Nazi movement, we highlight the core issues and themes around which the two movements have coalesced; identify key facilitating actors who have advanced the convergence of elements of the far right and the jihadist movements; and identify operational threats that emanate from this cross-ideological encounter.